2017
DOI: 10.1186/s12929-017-0397-x
|View full text |Cite
|
Sign up to set email alerts
|

H558R, a common SCN5A polymorphism, modifies the clinical phenotype of Brugada syndrome by modulating DNA methylation of SCN5A promoters

Abstract: BackgroundA common SCN5A polymorphism H558R (c.1673 A > G, rs1805124) improves sodium channel activity in mutated channels and known to be a genetic modifier of Brugada syndrome patients (BrS). We investigated clinical manifestations and underlying mechanisms of H558R in BrS.Methods and resultsWe genotyped H558R in 100 BrS (mean age 45 ± 14 years; 91 men) and 1875 controls (mean age 54 ± 18 years; 1546 men). We compared clinical parameters in BrS with and without H558R (H558R+ vs. H558R- group, N = 9 vs. 91). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
(42 reference statements)
2
32
0
Order By: Relevance
“…To our knowledge, the mutation of rs1805124 (H558R) has been reported to be associated with clinical disease (myocardial infarction, BrS, LQTS, etc. ), but no SCD‐related data have been reported in South China for this SNP mutation .…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, the mutation of rs1805124 (H558R) has been reported to be associated with clinical disease (myocardial infarction, BrS, LQTS, etc. ), but no SCD‐related data have been reported in South China for this SNP mutation .…”
Section: Discussionmentioning
confidence: 97%
“…14) For example, H558R polymorphism reduced the occurrence of ventricular fibrillation in patients with Brugada syndrome. 15) On the contrary, it reportedly exhibited LQT3-like dysfunction when it coexisted with SCN5A A572D, another missense variant in healthy subjects. 13) The functional analysis of SCN5A-mutation-positive Brugada syndrome demonstrated that the polymorphism attenuates the slow inactivation of sodium channel, which is enhanced by the coexisting pathogenic mutation of SCN5A.…”
Section: Discussionmentioning
confidence: 99%
“…13) The functional analysis of SCN5A-mutation-positive Brugada syndrome demonstrated that the polymorphism attenuates the slow inactivation of sodium channel, which is enhanced by the coexisting pathogenic mutation of SCN5A. 10) Matsumura, et al 15) demonstrated that SCN5A H 558R polymorphism modulated the clinical manifestations of Brugada syndrome. In their report, patients with H558 R showed a lower methylation level of SCN5A promoter and expressed higher levels of SCN5A in right atrial sections compared with patients without H558R.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the mutation also prevents VF in patients with BrS. [ 38 ] However, the mutation has not been shown to be associated with cardiac repolarization abnormalities, such as T-wave alternans. [ 39 ] These results indicate that rs1805124 is substitutable or does not directly affect the incidence of SCD.…”
Section: Discussionmentioning
confidence: 99%